2013
DOI: 10.3390/ijerph10083715
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and Its Treatments in Association with Autism Spectrum Disorders: A Review and Results from the CHARGE Study

Abstract: Previous findings on relationships between infertility, infertility therapies, and autism spectrum disorders (ASD) have been inconsistent. The goals of this study are first, to briefly review this evidence and second, to examine infertility and its treatments in association with having a child with ASD in newly analyzed data. In review, we identified 14 studies published as of May 2013 investigating infertility and/or its treatments and ASD. Overall, prior results showed little support for a strong association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
0
25
0
2
Order By: Relevance
“…This study was limited in that data regarding specific infertility conditions were not presented. A second case-control study of children residing in several regions in California reported similar proportions of maternal or paternal infertility diagnoses for children with ASD and typically-developing control children (Lyall et al 2013); however, specific infertility conditions could not be fully assessed because of very small numbers of both case and control mothers reporting individual infertility conditions. A third study, using a nested case-control design drawn from the Nurse's Health Study (NHS), which had a larger sample to assess individual conditions, also reported no association between infertility conditions and ASD (Lyall et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study was limited in that data regarding specific infertility conditions were not presented. A second case-control study of children residing in several regions in California reported similar proportions of maternal or paternal infertility diagnoses for children with ASD and typically-developing control children (Lyall et al 2013); however, specific infertility conditions could not be fully assessed because of very small numbers of both case and control mothers reporting individual infertility conditions. A third study, using a nested case-control design drawn from the Nurse's Health Study (NHS), which had a larger sample to assess individual conditions, also reported no association between infertility conditions and ASD (Lyall et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported no differences between ASD cases and typically developing controls in either ART use or use of various non-ART infertility treatments (Lyall et al 2013). Two other studies reported positive associations between use of non-ART ovulation induction medications and ASD, findings that were particularly noteworthy in that neither observed associations with ART, a treatment that nearly always includes high doses of ovulation induction medications (Lyall et al 2012; Hvidtjorn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations